Olfactory Proteins in Timema Stick Insects - Parker, Darren J.; Djordjevic, Jelisaveta; Schwander, Tanja (Frontiers in Ecology and Evolution, 2019)
Most animals use olfaction to obtain important information from the environment, including the presence of food or mates. Insects detect odorants through receptors that are expressed in the sensory neurons of olfactory sensilla, which cover the surface of the antennae. The olfactory capacities of an insect thus depend largely on the repertoire of odorant receptors. Here we study the repertoire of olfactory proteins in the stick insect Timema cristinae. We first generate transcriptomes from antennae of adult males and females and identify, via homology searches, putative olfactory proteins of three different families: odorant binding proteins, odorant receptors and chemosensory proteins. We then attempt to categorize olfactory proteins likely involved in sexual communication by comparing gene expression between adults and juveniles, as well as between males and females. Notably, olfactory proteins involved in perception of food or abiotic environmental components should be expressed in both adults and juveniles. By contrast, olfactory proteins involved in sexual communication, such as the detection of sex pheromones, should be expressed in adults and often comprise different repertoires in males and females. Finally, we also tested whether olfactory proteins in general and the subset with putative roles in sexual communication in particular are under relaxed selection in the asexual species T. monikensis, a close relative of T. cristinae. We find that olfactory proteins are typically differentially expressed between juveniles and adults, but there is little overlap of differential expression between developmental stages and the level of sex bias in adults. Furthermore, while we find evidence that olfactory proteins are indeed under relaxed selection in the asexual species, there is no evidence that this is particularly the case for olfactory genes with a putative role in sexual communication. Nevertheless, the list of olfactory genes generated in our study provides a useful tool for future studies on olfaction in Timema and other stick insects.